IMPLEMENTASI PELAYANAN PUBLIK MELALUI SIMAS MANDIRI (SISTEM MASYARAKAT MELAYANI SENDIRI) DALAM MEWUJUDKAN SMART KAMPUNG (STUDI DI DESA PESUCEN KABUPATEN BANYUWANGI) - Romy Ardiyanto; Dimas Imaniar; Safrieta Jatu Permatasari (Yayasan Nusantara Hasana Berdikari, 2024)
The smart village concept is one form of e-government implementation at the village level in Banyuwangi Regency. The utilization of information technology is carried out to create effective, efficient, transparent services in accordance with the basis of e-government. The Self-Service Community System (Simas Mandiri) is a supporting tool for the smooth running of the smart village program. The research method used in this research is qualitative research and is descriptive. Simas Mandiri is included in the scope of the smart village work program in the field of Public Services. The application of the smart kampung concept is expected to encourage villages to continue to strive to develop e-government, which is currently used as the basis for services not only at the district level, but also in all villages in Banyuwangi Regency. Based on the research, it can be concluded that the implementation of the Self-Service Community System (Simas Mandiri) program in Pesucen Village, Kalipuro District, Banyuwangi Regency has been running well, because the Pesucen Village Head is very supportive of this program. The support provided is in the form of providing adequate resources, but there are several obstacles in its implementation. The obstacle faced by this program is the absence of a bureaucratic structure in the implementation of the Self-Service Community System (Simas Mandiri) program. This has an impact on internal communication in the implementation of this program.